Analysis of Monetary Policy, Capital, Saving, FDI, and Economic Development for High and Middle Income Economies with ARDL Approach (Global Journal of Management and Business Research, 2020)
Monetary policy and macroeconomic factors play a decisive and fascinating role to determine the economic output of the country. Policymakers and economists take very seriously and consider them deterministic because these factors have an influence on each other. Therefore, the research has the objective to delineate the effect of monetary policy and all given indicators together on economic development precisely and their interdependence as well. ARDL (Autoregressive Distributed Lag) Bounds test cointegration technique is applied by employing annual time series data from 1980 to 2018. Money supply, lending interest rate, inflation, capital, saving, FDI, and economic development are said to be independent variables and explanatory variables one by one for each country separately to ascertain their interdependence.
Keywords: monetary policy; capital; savings; foreign direct investment; economic development; ARDL ECM mechanism; and granger causality